The history of the breeding work on winter durum wheat development: results, problems, prospects - N. E. Samofalova; N. P. Ilichkina; O. A. Dubinina; T. S. Makarova; O. A. Kostylenko; A. S. Kameneva; T. G. Derova; N. S. Kravchenko (Зерновое хозяйство России, 2020)
The current paper has considered the results of sixty years of breeding work on winter durum wheat development, a new grain crop for the steppe arid conditions of the Don area. This breeding period was represented by five stages, each of them was characterized by the solution of various problems, by the development of methods for obtaining and using the initial material and, on its basis, varieties being urgent for the definite period. Throughout the history of breeding work there were developed 32 winter turgid and durum wheat varieties, 21 of which were zoned or included into the State List, 16 were protected by patents, 6 were studied at the SVT. There have been presented the study results of the varieties of different breeding stages according to their main economically valuable traits and properties, obtained in the trial ‘History of the breeding work’ with green manure fallow in 2015–2019. There have been identified their positive advantages and disadvantages in the breding process. Significant progress has been achieved in changing plant architectonics by reducing straw length on 39.3–45.2 cm, increasing the resistance to lodging on 1.3–1.4 points, improving the agrocenosis on 300–400 heads per m2, and increasing the harvesting index from 26.1 to 41.1%. Productivity due to productive breeding for 60 years increased on 3.37 t/ha or 66.3%, and the productivity potential of the modern short-stemmed varieties reached 10 t/ha and more. There has been found out that productivity improvement during breeding positively affected on adaptive properties (winter resistance, drought resistance, resistance to brown and yellow rust, powdery mildew) and the indices grain and pasta quality. There have also been indicated the problematic areas which require further intensive work not only in breeding, but also in a wider distribution of the winter durum wheat varieties in agricultural production.